Cycloplegic Versus Manifest Refractions - Hensel, Gordon (Canadian Journal of Optometry, 1982)
With the precedent set by the New Brunswick Optometric Association and upcoming changes in drug legislation in several western provinces; optometrists across Canada are becoming increasingly aware of the use of diagnostic pharmaceuticals. The following report compares the refractive status of 423 eyes when examined by manifest and cycloplegic refractions. The subjects ranged in age from 2 to 89 years, and 62% were female.